2014
DOI: 10.1016/j.psychres.2014.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia in schizophrenia: Associations with neurocognition and emotional distress

Abstract: While alexithymia, or difficulties identifying and describing affect, has been commonly observed in schizophrenia, little is known about its causes and correlates. To test the hypothesis that deficits in emotion identification and expression result from, or are at least related to, deficits in neurocognition and affective symptoms, we assessed alexithymia using the Toronto Alexithymia Scale (TAS-20), symptoms using the Positive and Negative Syndrome Scale (PANSS), and neurocognition using the MATRICS battery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 53 publications
2
32
1
1
Order By: Relevance
“…Similarly, Patterson et al (2005) found Hispanics scored significantly worse than Caucasians even when controlling for age and severity of illness. However, Bengoetxea et al (2014) found no significant differences between monolingual Spanish speaking Hispanics, English-speaking Hispanics, and English-speaking non-Hispanics.…”
Section: Introductionmentioning
confidence: 56%
“…Similarly, Patterson et al (2005) found Hispanics scored significantly worse than Caucasians even when controlling for age and severity of illness. However, Bengoetxea et al (2014) found no significant differences between monolingual Spanish speaking Hispanics, English-speaking Hispanics, and English-speaking non-Hispanics.…”
Section: Introductionmentioning
confidence: 56%
“…Alexithymia has traditionally been studied with respect to its comorbidity with neurodevelopmental disorders such as autism spectrum disorders (Bird and Cook, 2013) and schizophrenia (Fogley et al, 2014), but recent studies have suggested that alexithymia can be acquired following brain injury (Henry et al, 2006; Williams and Wood, 2013, 2010). The present findings extend this work by showing that alexithymia can be acquired following injuries to the AI specifically, with more pronounced lesions being associated with greater impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The emotional symptoms of a variety of disorders have been linked to co-occurring alexithymia, such as autism (Bird et al, 2010), eating disorders (Brewer et al, 2015a), and schizophrenia (Fogley et al, 2014), suggesting that intact awareness of one’s own emotions might be critical to mental health. The potential translational value of this work has led to an increasing interest in alexithymia both in the public (Robson, 2015; Serani, 2014) and scientific (Bird and Cook, 2013; Lane et al, 2015) literatures, yet the neurocognitive impairments that lead to alexithymia remain unclear.…”
mentioning
confidence: 99%
“…This in turn, is thought to increase their reliance on maladaptive behaviours such as binging and purging, to regulate distress (Barrett, Gross, Christensen, & Benvenuto, 2001;Sheppes, Suri, & Gross, 2015;Tull & Aldao, 2015;Whiteside et al, 2007). This argument is supported through several independent lines of enquiry; (1) individuals who engage in disordered eating experience increased difficulties in identifying emotions and/or distinguishing between them (i.e., LEC; Bydlowski et al, 2005;Speranza, Loas, Wallier, & Corcos, 2007); (2) LEC has been associated with increased distress (Fogarty, Warman, & Lysakerm, 2015); (3) increased distress has been identified as a precipitant to disordered eating particularly in individuals who show emotion regulation difficulties (Berner et al, 2017;Haynos & Fruzzetti, 2011;Lavender et al, 2016).…”
mentioning
confidence: 99%